Population health and status of epidemiology: WHO European Region I - AY, NADİYE PINAR (OXFORD UNIV PRESS, 2013)
Background This article of the International Epidemiological Association commissioned paper series stocktakes the population health and status of epidemiology in 21 of the 53 countries of the WHO European Region. By United Nations geographical classification, these countries belong to Eastern Europe, Western Asia and South-Central Asia. Methods Published data were used to describe population health indicators and risk factors. Epidemiological training and research was assessed based on author knowledge, information searches and E-mail survey of experts. Bibliometric analyses determined epidemiological publication outputs. Results Between-country differences in life expectancy, amount and profile of disease burden and prevalence of risk factors are marked. Epidemiological training is affected by ongoing structural reforms of educational systems. Training is advanced in Israel and several Eastern European countries. Epidemiological research is mainly university-based in most countries, but predominantly conducted by governmental research institutes in several countries of the former Soviet Union. Funding is generally external and limited, partially due to competition from and prioritization of biomedical research. Multiple relevant professional societies exist, especially in Poland, the Czech Republic and Hungary. Few of the region's 39 epidemiological academic journals have international currency. The number of epidemiological publications per population is highest for Israel and lowest for South-Central Asian countries. Conclusions Epidemiological capacity will continue to be heterogeneous across the region and depend more on countries' individual historical, social, political and economic conditions and contexts than their epidemiologists' successive efforts. National and international research funding, and within- and between-country collaborations should be enhanced, especially for South-Central Asian countries.
Keywords: European region; epidemiology; disease burden; epidemiological research; epidemiological training; FORMER SOVIET-UNION; HAZARDOUS ALCOHOL-DRINKING; PUBLIC-HEALTH; EASTERN-EUROPE; LIFE EXPECTANCY; SOCIOECONOMIC INEQUALITIES; EDUCATIONAL INEQUALITIES; INFANT-MORTALITY; RUSSIA; COUNTRIES